THE PROBLEM OF TRANSLATING REALITY IN LITERARY TRANSLATION (On the example of the horror story by A. Qahhoring) - Dilrabo Turakulova; Xodjayeva N. (Journals Park Publishing, 2022)
The article analyzes the translation of A. Qahhor's story into Korean, especially the expression of Uzbek national characteristics in Korean.The article analyzes the translation of A. Qahhor's story into Korean, in particular, the expression of Uzbek national features in Korean.
Keywords: Reality; original word; transformation